The Influence of Return on Assets (ROA), Debt to Equity Ratio (DER), Current Ratio (CR), Debt to Asset Ratio (DAR) On Stock Returns in Food and Beverage Sector Manufacturing Companies Listed on The Indonesia Stock Exchange for The Period 2018 - 2022 - Herlin Munthe; Novita Royana Marbun; Yara Ainy br Ginting; Kiki Hardiansyah Siregar (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
This study seeks to examine the impact of Return on Asset (ROA), Debt to Equity Ratio (DER), Current Ratio (CR), and Debt to Asset Ratio (DAR) on Stock Return in manufacturing companies within the food and beverage industry sector listed on the Indonesia Stock Exchange from 2018 to 2022. The study will analyze the relationship between these variables both individually and simultaneously. The approach employed in this study is a quantitative methodology. From 2018 to 2019, 28 food and beverage industry production enterprises comprised 80 samples. This study utilized purposive sampling and employed various statistical tests, including the partial t-test, simultaneous F-test, classical assumption test, and adjusted R-square test. The test results indicate a significant relationship between Return on Assets (ROA) and Return on Sales (RS), as evidenced by the p-value of 0.003, which is less than the significance level of 0.05. (2) In the SPSS T-test, a sig value of 0.499>0.05 indicates no significant influence of DER on RS. (3) The results of the SPSS testing using the T-test show that the significance value is 0.484, more significant than 0.05. This condition indicates that CR does not have a significant influence on RS. (4) Based on the findings of the statistical significance test (p-value of 0.134>0.05), it may be inferred that DAR does not have a significant influence on RS. The calculated value of f, 4.664, is greater than the critical value of 2.49, and the significance level of 0.003 is less than the threshold of 0.05. Therefore, we can infer that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. The Adjusted R Square value is 0.194, indicating that the independent variables can explain 19.4% of the variation in Y (RS). Other factors influence the remaining 80.6% of the variation.